Effect of Temperature on Tooth Staining by 0.12% Chlorhexidine Gluconate - Carey, Clifton M.; Yagudayev, Arthur; Font, Kerri (Frontiers in Dental Medicine, 2021)
Introduction: Natural color of dentin is affected by many variables, including anatomical variations, age, how much dentin is exposed, or how much enamel is covering the dentin. Chlorhexidine gluconate (CHX) has been observed to cause tooth staining, especially of exposed dentin. Risk factors for CHX staining include the amount of time for CHX utilization amongst others. Interestingly, the temperature of the rinse when used has been identified as a risk factor. However, no evidence of the effect of temperature is available in the literature. The purpose of this study was to determine the effect of temperature on dentin staining due to CHX exposure. Methods: Two studies were done. The first a pilot study at room temperature to determine the time needed to establish staining solutions, a method to evaluate stain intensity, and establish the time needed to stain dentin samples in vitro. The second study exposed dentin samples on a twice daily basis to a 1 min soak in CHX at different temperatures, followed by a period in an unstimulated saliva mixed with black tea mixture. Temperatures tested were 4, 23, 37 and 50°C. Control samples were exposed to only black tea and saliva (no CHX) and tested at 23°C. Results: The pilot study found that the combination of CHX and black tea causes dentin staining. From this data the sample size needed for the second experiment was calculated, requiring 12 samples per group. Sixty dentin samples were divided amongst 5 groups. The data from this study showed significant darkening of the dentin samples over 18 days. The 4 and 23°C CHX rinses resulted in significant staining compared to the control samples. The 37 and 50°C CHX rinses did not stain significantly more than the control samples. Conclusions: Chlorhexidine has the ability to cause tooth staining in the presence of chromogens such as those in black tea. Significant darkening was observed at lower temperatures (4 and 23°C) over 18 days, therefore dental professionals may wish to advise gently warming the CHX rinse toward 37°C prior to use to reduce the risk of staining.